Boosting Purchase Intention and Online Participation Through Passion - Herrando, Carolina; Jiménez-Martínez, Julio; De Hoyos, María José Martín (International Journal of Informatics and Information Systems, 2020)
This study analyzes the role of passion in engaging users and how it affects purchase intention and participation in social commerce contexts. Based on marketing research, the engagement generation process is studied through the interactions among social presence,interactivity, enjoyment, sPassion, purchase intention and spread of sWOM. The results have empirically confirmed that social interactions and information exchange derived from the process boost user participation and the intention to purchase. At the core of the process, sPassion positively affects the spreading of sWOM. The introduction of the new concept sPassion brings new challenges and opportunities to marketing research, helping to develop the concept of engagement and furthering research on WOM valence. Knowing how sPassion is formed and what factors are key to its creation enable companies to understand the necessary steps to enhance user participation in social commerce contexts.